P38 Risk and protective factors for psychotic experiences in adolescence: a population-based study. (3rd September 2019) - McMahon, E; Corcoran, P; Keeley, H; Clarke, M; Coughlan, H; Wasserman, D; Hoven, C; Carli, V; Sarchiapone, M; Cannon, M
Abstract : Background: Psychotic experiences (PEs) are reported by a significant minority of adolescents and are associated with the development of schizophrenia and other psychiatric disorders in adulthood. Few modifiable protective factors have been identified to date. The aims of this study were to examine associations between a range of psychopathological, adverse life event, coping and social support factors and PEs in a general population sample of Irish adolescents. Methods: Cross-sectional data were drawn from the Irish centre of the Saving and Empowering Young Lives in Europe (SEYLE) study (German Clinical Trials Registry, DRKS00000214). Students were administered a classroom-based self-report questionnaire and 973 adolescents, of whom 522 (53.6%) were boys, participated. Psychotic experiences were assessed using the 7-item Adolescent Psychotic Symptom Screener. Results: Of the total sample, 81 (8.7%) of the sample were found to be at risk of PEs. A wide range of factors from adverse life event, lifestyle and mental health domains had crude associations with PEs, while parental support was associated with lower prevalence of PEs. In multivariate analysis, independent associations were found between PEs and the number of adverse life events experienced (OR: 1.61; CI: 1.29–2.02; p<0.0005) as well as maladaptive/pathological internet use (OR: 2.60; CI: 1.15–5.89; p=0.02). Positive parental support was associated with reduced risk of PEs after adjustment for established risk factors (OR: 0.40; CI: 0.18–0.90; p=0.03) and so offers a potential protective role. Conclusion: These findings can inform the development of optimal interventions for adolescents at risk of psychopathology and their families.